Potential Inhibition of Human Neutrophil Elastase Enzyme to Attenuate Emphysema; A Molecular Docking Study (Molecular Medicine Communications, 2024)
Chronic Obstructive Pulmonary Disease (COPD), also referred to as chronic bronchitis and emphysema, is a major threat to global health. It is an essential part of the Rehabilitation 2030 initiative of the World Health Organization (WHO). It is more common in nations with enhanced smoking habits. The latter is associated with the damage of the elastin protein of the lung parenchyma as a result of the enhanced protease activity of human neutrophil elastase (HNE). This leads to impaired gaseous exchange and air entrapment in the lungs. Among symptomatic pharmacotherapy, anti-proteases such as alpha-1 antitrypsin could be used to counter the effect of proteases, but the treatment costs too much and is not easily available. This study aims to explore and discover potential drug compounds for lessening the progression of protease-induced lung parenchymal damage in emphysema. Molecular docking and ADMET analysis investigated the anti-HNE activity of several compounds and newly designed analogs of Sivelestat, a drug molecule that has been approved as Sivelestat Sodium Hydrate in Japan as well as in the Republic of Korea for the management of acute lung injury. The software used in this study were PyRx, BIOVIA Discovery Studio Visualizer v17.2.0.16349, and DataWarrior V5.5.0. All the potential drug molecules demonstrated binding with the active residues of HNE, i.e., Ser 195, His 57, and Ser 214, and showed potentially promising results in terms of their binding energies and poses. Subsequent in vitro and in vivo studies are recommended to support the findings of this study
Keywords: Human Neutrophil Elastase; Molecular Docking; In silico ADMET; Emphysema; COPD